Nasional Challenges In Curriculum Planning Amidst Changes In National Education Policy - RISKY ARYSKA PUTRI RY; SUPRATMAN ZAKIR; JANUAR; NURUL MAWADDAH AL-MURSAL; RHAFIIQUL AZHARI KARIM (BiCED Proceeding, 2024)
This study aims to identify and analyze the challenges faced in curriculum planning in the midst of changing national education policies. The background of the problem relates to the frequent and rapid changes in education policies, which force the education system to adapt quickly, while schools and educators are generally unprepared for these changes. The main question posed in this study is: “What are the challenges faced in curriculum planning amidst changes in national education policy?” This research makes a new contribution by identifying challenges that are not only related to the technical aspects of the curriculum but also to educators' readiness, infrastructure limitations and the complexity of education policy changes. To answer these questions, this research used a qualitative design with a case study approach in several schools, involving in-depth interviews with teachers, principals and education officials. This methodology enabled in-depth data collection on the challenges faced in curriculum implementation on the ground. The main results show that the biggest challenges in curriculum planning are the unpreparedness of educators in implementing the new curriculum, the lack of supporting facilities and the uncertainty that comes with rapid policy changes. The study recommends continuous training for educators, improved education infrastructure and more stable and well-planned policies.